PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA PADA PEGAWAI KP2KP GUNUNGSITOLI - PEMILMAN ZEBUA; FATOLOSA HULU; ENVILWAN BERKAT HAREFA (LP2MTBM MAKARIOZ, 2022)
This study aims to analyze the effect of human resource competence on employee performance. The competence of an employee is certainly related to the performance of the employee himself. One of the factors that have an influence on employee performance in KP2KP is the competence of human resources. The research method used is quantitative with a survey method to determine the effect of the variable of human resource competence with the variable of performance on employees. The population in this study were employees of KP2KP Gunungsitoli. Regression test using SPSS 22 is used for hypothesis testing. The results of the study show that there is a significant influence between human resource competence and employee performance, this is evidenced by the positive regression coefficient of human resource competence of 9.218. In the t test, the value of t arithmetic > t table (9.218 > 0.691), meaning that partially there is a significant influence between human resource competence on employee performance at KP2KP Gunungsitoli. evidenced by the results of correlation analysis obtained R of 0.931, which indicates that there is a strong relationship between human resource competence and employee performance, namely rcount = 0.931 and rtable = 0.514, where obtained 0.931> 0.514.